Analisis Literasi Matematika Siswa Kelas X Berdasarkan Gaya Belajar di SMAN 1 Sakra Timur - Atmaja, Muh Subakti; Hayati, Laila; Kertiyani, Ni Made Intan (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2025)
Mathematical literacy is one of the essential competencies of the 21st century, playing a crucial role in fostering critical thinking and problem-solving skills. However, initial assessments indicate that students’ mathematical literacy skills remain relatively low, partly influenced by differences in learning styles. This study aims to describe the mathematical literacy abilities of tenth-grade students at SMAN 1 Sakra Timur in the 2025/2026 academic year, viewed from visual, auditory, and kinesthetic learning styles. The research employed a qualitative descriptive method with subjects selected through purposive sampling. Data were collected using a learning style questionnaire, a mathematical literacy test based on trigonometric contexts, and in-depth interviews, then analyzed through data reduction, presentation, and conclusion drawing. The findings reveal that students’ mathematical literacy skills were generally at a low level, with visual learners tending to achieve a medium level, auditory learners ranging from low to medium, and kinesthetic learners showing variation from low to high. These results highlight a strong relationship between learning style characteristics and mathematical literacy performance. In conclusion, developing adaptive instructional strategies tailored to students’ learning styles is crucial to optimizing mathematical literacy skills.